The demand for global and local environmental protection: Experimental evidence from climate change mitigation in Beijing - Andreas Loeschel; Jiansuo Pei; Bodo Sturm; Ran Wang; Wolfgang Buchholz; Zhongxiu Zhao (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2018)
In this study, the real demand for global and local environmental protection in Beijing, China, is elicited and investigated. Participants from Beijing were offered the opportunity to contribute to voluntary climate change mitigation by purchasing permits from two Chinese CO2 emissions trading schemes (ETS). Purchased permits were withdrawn from the ETS. Since CO2 emissions mitigation is inevitably linked to other local benefits like the reduction in emissions of air pollutants, the aim of our study is to establish the demand for local and global environmental protection. To this end, Beijing and Shenzhen ETS permits were offered. The result is that at low prices the demand for Beijing ETS permits is significantly higher than for Shenzhen ETS permits indicating that a substantial part of the revealed demand for voluntary climate change mitigation in Beijing is driven by concerns for local co-benefits of CO2 emissions reduction. Our research identifies the important role of private benefits in the voluntary provision of the global public good climate change mitigation and provides first experimental evidence for China.
Keywords: 330